2015
DOI: 10.4314/tjpr.v14i6.22
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum Beta-Lactamase (ESBL)–Producing Gram-negative Isolates from Urine and Wound Specimens in a Tertiary Health Facility in Southern Nigeria

Abstract: Purpose: To determine the prevalence of extended spectrum beta lactamase (ESBL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
21
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 19 publications
10
21
6
Order By: Relevance
“…Wound and urinary specimens form the largest group of clinical specimens received in microbiology laboratories as was the case in this study. 9 Our finding compares with previous studies which have shown that most GNB recovered from urine and wounds are ESBL-producing and another in which urine samples had the highest prevalence of MBL producing bacteria. 3,9 The carbapenems (imipenem and meropenem) which were the most effective antibiotics in this study showed activity against ESBL and AmpC β-lactamase producing GNBs.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Wound and urinary specimens form the largest group of clinical specimens received in microbiology laboratories as was the case in this study. 9 Our finding compares with previous studies which have shown that most GNB recovered from urine and wounds are ESBL-producing and another in which urine samples had the highest prevalence of MBL producing bacteria. 3,9 The carbapenems (imipenem and meropenem) which were the most effective antibiotics in this study showed activity against ESBL and AmpC β-lactamase producing GNBs.…”
Section: Discussioncontrasting
confidence: 56%
“…9 Our finding compares with previous studies which have shown that most GNB recovered from urine and wounds are ESBL-producing and another in which urine samples had the highest prevalence of MBL producing bacteria. 3,9 The carbapenems (imipenem and meropenem) which were the most effective antibiotics in this study showed activity against ESBL and AmpC β-lactamase producing GNBs. The carbapenems are expensive drugs of last resort in our region and have shown good activity against GNB producing both enzymes.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations